Strategi Penguatan Ukhuwah Islamiyah melalui Perlombaan Shalat Berjamaah Jamaah ‘Aisyiyah : Studi Kegiatan KKN Nasional Universitas Muhammadiyah Makassar di Surabaya - Andi Almira Aprilia Ramli; Fatiama Fatiama; Wahyuni Suryaningtyas; Syarifuddin Syarifuddin (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Prayer (shalat) is the central act of worship in Islam and holds a fundamental role in nurturing the spiritual life of Muslims. However, in practice, challenges often arise within society, particularly regarding the accuracy of recitations, movements, and the cohesiveness of congregational prayer. Thus, the urgency of understanding correct fiqh shalat remains crucial to ensure the quality of worship and strengthen ukhuwah islamiyah (Islamic brotherhood). In response to this need, students of Universitas Muhammadiyah Makassar, through the National Community Service Program (KKN) in Surabaya, organized a community engagement activity under the theme of Kemuhammadiyahan, namely a congregational prayer competition involving members of ‘Aisyiyah. The aim of this activity was to internalize Muhammadiyah values, enhance the understanding of fiqh shalat according to Islamic teachings, and foster a spirit of togetherness through an educational and participatory approach. The competition was assessed based on prayer movements, recitations, and group cohesiveness. The results revealed active participation and high enthusiasm from the participants, who not only competed but also learned to improve the quality of their worship. This activity successfully created a positive religious atmosphere, strengthened bonds among community members, and affirmed the role of KKN as a medium of community service that integrates religious education, Islamic propagation (dakwah), and spiritual development rooted in progressive Islamic values.